HLA-DM Focuses on Conformational Flexibility Around P1 Pocket to Catalyze Peptide Exchange - Yin, Liusong; Stern, Lawrence J. (Frontiers in Immunology, 2013)
Peptides presented by major histocompatibility complex class II (MHCII) molecules to CD4+ T cells play a central role in the initiation of adaptive immunity. This antigen presentation process is characterized by the proteolytic cleavage of foreign and self proteins, and loading of the resultant peptides onto MHCII molecules. Loading and exchange of antigenic peptides is catalyzed by a non-classical MHCII molecule, HLA-DM. The impact of HLA-DM on epitope selection has been appreciated for a long time. However, the molecular mechanism by which HLA-DM mediates peptide exchange remains elusive. Here, we review recent efforts in elucidating how HLA-DM works, highlighted by two recently solved co-structures of HLA-DM bound to HLA-DO (a natural inhibitor of HLA-DM), or to HLA-DR1 (a common MHCII). In light of these efforts, a model for HLA-DM action in which HLA-DM utilizes conformational flexibility around the P1 pocket of the MHCII-peptide complex to catalyze peptide exchange is proposed.